2017
DOI: 10.1186/s12199-017-0681-0
|View full text |Cite|
|
Sign up to set email alerts
|

Association between NAT2, CYP1A1, and CYP1A2 genotypes, heterocyclic aromatic amines, and prostate cancer risk: a case control study in Japan

Abstract: BackgroundHeterocyclic aromatic amines (HAAs) may confer prostate cancer risk; however, the evidence is inconclusive and the activity of HAA-metabolizing enzymes is modulated by gene variants. The purpose of our study was to determine whether there was evidence of an association between HAA intake, polymorphisms in NAT2, CYP1A1, and CYP1A2 and prostate cancer risk in Japanese men.MethodsSecondary data analysis of an observational case control study was performed. Among 750 patients with prostate cancer and 870… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These enzymes metabolize polycyclic aromatic hydrocarbons, arylamines, and N-heterocyclics that are found in grilled food or meat cooked at high temperatures. These molecules can be carcinogenic and toxic when accumulated in the organism [41, 42]. Three independent studies found evidence of positive selection in CYP1A2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes metabolize polycyclic aromatic hydrocarbons, arylamines, and N-heterocyclics that are found in grilled food or meat cooked at high temperatures. These molecules can be carcinogenic and toxic when accumulated in the organism [41, 42]. Three independent studies found evidence of positive selection in CYP1A2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The NAT2 acetylated genotype has a large influence on cancer predisposition and may induce susceptibility to tumors arising from industrial and environmental aryl amines (Mitchell, 2019). To date, a limited number of studies have been published in Sudan concerning inter-individual and inter-ethnic differences in NAT2 allele frequencies, (Ali et al, 2019;Al-Yahyaee et al, 2007) but this is the first investigation into its genetic variations (481 C→T, 590 G→A, 803 A→G and 857G→A) and their association with CML susceptibility and progression (Kotila et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Of the 50 known P450 isoenzymes catalyzing drug metabolism, more than 20 P450 genes are functionally polymorphic, such as CYP2A6, CYP2C9, CYP2C19, CYP2D6, CYP1B1, and CYP1A2. The polymorphic P450s catalyze about 40% of the drug metabolism [119,135]. In addition, P450 polymorphisms were reported to confer susceptibility to disease and disease protection or reduced risk (Table 3).…”
Section: Role Of P450s In Chemotherapymentioning
confidence: 99%